THE INFLUENCE OF TIE POINTS DISTRIBUTION IN UAV PHOTOGRAMMETRY - NOVIANTI BANI (NIM : 25116001), MARTINCE
The availability of geospatial information is the one factor to optimize the development planning. On the other hand, increasing the requirement of large-scale maps continues to be pursued to fulfil these challenges. One of the efforts is to perform this requirement through utilize the mapping technology using UAV. Mapping using UAV is considered effective and efficient both in terms of time and cost. The accuracy of the data that generated from UAVs has continuously improved. One of them is conducting a study of the data that produced by the UAV vehicles through studied about the influence of tie points distribution in UAV Photogrammetry and its effect on the map accuracy. This study shows that the effect of the influence of tie points distribution that extracted using image matching methods and the experiments with the various number of tie points in Von Gruber location would give a significant reduction in the average error in the image space. In addition, The Damped Bundle Adjustment (DBAT) can be used to provide independent verification of the Bundle Adjustment computation. The study which conducted at the tie points in the Von Gruber area using the extraction window starting respectively from 301x301 pixels, 401x401 pixels, 501x501 pixels, 601x601 pixels, and 701x701 pixels shows that the best RMSE is in the 601x601 pixel window. The RMSE of Delta XY is 0.16 m. Based on the RMSE value, the geometry result of the map fulfil the standards based on Peraturan Kepala Badan Informasi Geospasial No. 15, 2014, with the scale map 1: 1000 in the class I.